2020
DOI: 10.1111/aogs.13842
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of non‐invasive prenatal testing for trisomies 21, 18 and 13 in twin pregnancies: A cohort study and a systematic meta‐analysis

Abstract: Introduction:The objective of this study was to report on the clinical performance of non-invasive prenatal testing (NIPT) for trisomies 21, 18 and 13 in twin pregnancies and to define the performance of NIPT by combining our cohort study results with published studies in a systematic meta-analysis. Material and methods:A cohort study was carried out in the First Affiliated Hospital of Sun Yat-sen University and Kanghua Hospital. Meanwhile, searches of PubMed, EMBASE, The Cochrane Library and Web of Science fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The literature search identified 381 potentially relevant citations, but 366 were excluded because they were not relevant, a conference abstract rather than a peer‐reviewed paper, a review article, an opinion, not confined to twins, a case–control study, a study on clinical implementation of cfDNA testing in screening for aneuploidy in which pregnancy outcome data were provided for fewer than 85% of the study population or a proof‐of‐principle study reporting laboratory techniques rather than clinical validation of a predefined method of maternal blood cfDNA analysis (Figure 2). In total, 15 relevant studies were identified 2,13–26 but three of these 2,13,14 were excluded from the meta‐analysis because their data are included in the updated FMF results presented above. The characteristics of our current study and the 12 studies identified by the literature search are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search identified 381 potentially relevant citations, but 366 were excluded because they were not relevant, a conference abstract rather than a peer‐reviewed paper, a review article, an opinion, not confined to twins, a case–control study, a study on clinical implementation of cfDNA testing in screening for aneuploidy in which pregnancy outcome data were provided for fewer than 85% of the study population or a proof‐of‐principle study reporting laboratory techniques rather than clinical validation of a predefined method of maternal blood cfDNA analysis (Figure 2). In total, 15 relevant studies were identified 2,13–26 but three of these 2,13,14 were excluded from the meta‐analysis because their data are included in the updated FMF results presented above. The characteristics of our current study and the 12 studies identified by the literature search are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 12 studies reporting on screening for trisomy in twin pregnancies by cfDNA testing of maternal blood, in addition to our previous studies, the data from which are included in the current FMF study. The main features of these 12 studies are, first, the method of cfDNA testing was by MPSS in 11 studies and by targeted testing in only one, second, none of the studies was confined to the first trimester and, in some cases, testing was carried out as late as 36 weeks' gestation 16,26 , and, third, in nine of the studies, the cfDNA test provided a result in > 99% of cases 15–18,20,22,23,25,26 and, in six of the studies, pregnancy outcome was apparently obtained in > 99% of cases 14,16,18,21,23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective study of the efficacy of noninvasive prenatal testing (NIPT) of twin pregnancies for trisomy 21 (Down syndrome), trisomy 18 (Edwards' syndrome) and trisomy 13 (Patau syndrome) is of interest. The work was conducted by He et al (2020), who represent a number of universities and hospitals in China. The researchers asserted that prenatal screening of multiple pregnancies is becoming increasingly important because such conceptions are rising due to advances in reproductive technology.…”
Section: Trisomies In Twin Pregnanciesmentioning
confidence: 99%